Data mining for Customer Relationship Management - Berry, Michael J. A. (Henry Stewart Talks, 2008)
Businesses should establish a learning relationship with their customers, Data mining is a key enabler of the learning relationship, Business processes are organized around the customer relationship, Business processes generate data that can be used for modeling, Product penetration, Campaign response, Campaign profitability, Differential response analysis, Customer value, Recommendation and cross-selling, Forecasting remaining customer lifetime
Archived at 2022/03/17